Dynamic atmospheric chamber systems: applications to trace gas emissions from soil and plant uptake. (26th June 2006) - Aneja, Viney P.; Blunden, Jessica; Claiborn, Candis S.; Rogers, Hugo H.
Atmospheric emissions, transport, transformation and deposition of trace gases may be simulated through chambers. The dynamic flow-through chamber system has been developed in response to a need to measure emissions of nitrogen, sulphur and carbon compounds for a variety of field applications. Oxides of nitrogen (NO, NO2, NOY ) emissions have been measured from agricultural fertilised/unfertilised soils. Ammonia-nitrogen (NH3 –N) and reduced organic sulphur compound emissions have been measured using this same technique across a gas-liquid and soil-atmosphere interface at swine waste treatment anaerobic storage lagoons and in agricultural fields. Similar chamber systems have also been deployed to measure the uptake of nitrogen, sulphur, ozone and hydrogen peroxide gases by crops and vegetation to examine atmospheric-biospheric interactions. Emission measurements compare well with a coupled gas-liquid transfer with chemical reaction model as well as a US Environmental Protection Agency (EPA) WATER9 model.